A non-invasive method for detecting the metabolic stress response in rodents: characterization and disruption of the circadian corticosterone rhythm - Thanos, P K; Cavigelli, S A; Michaelides, M; Olvet, D M; Patel, U; Diep, M N; Volkow, N D (Physiological research, 2009)
Plasma corticosterone (CORT) measures are a common procedure to detect stress responses in rodents. However, the procedure is invasive and can influence CORT levels, making it less than ideal for monitoring CORT circadian rhythms. In the current paper, we examined the applicability of a non-invasive fecal CORT metabolite measure to assess the circadian rhythm. We compared fecal CORT metabolite levels to circulating CORT levels, and analyzed change in the fecal circadian rhythm following an acute stressor (i.e. blood sampling by tail veil catheter). Fecal and blood samples were collected from male adolescent rats and analyzed for CORT metabolites and circulating CORT respectively. Fecal samples were collected hourly for 24 h before and after blood draw. On average, peak fecal CORT metabolite values occurred 7-9 h after the plasma CORT peak and time-matched fecal CORT values were well correlated with plasma CORT. As a result of the rapid blood draw, fecal production and CORT levels were altered the next day. These results indicate fecal CORT metabolite measures can be used to assess conditions that disrupt the circadian CORT rhythm, and provide a method to measure long-term changes in CORT production. This can benefit research that requires long-term glucocorticoid assessment (e.g. stress mechanisms underlying health).
Keywords: Stress, Physiological; Corticosterone; Animals; pohybová aktivita; Iodine Radioisotopes; mužské pohlaví; Rats; Energy Metabolism; radioimunoanalýza; Rats, Sprague-Dawley; feces; radioizotopy jodu; Circadian Rhythm; fyziologický stres; Defecation; Radioimmunoassay; cirkadiánní rytmus; kortikosteron; Feces; zvířata; defekace; potkani Sprague-Dawley; energetický metabolismus; krysa rodu Rattus; Motor Activity; Male